Influencing the Utilization of Dental Health Services at Rengas Pulau Public Health Center - Chrismis Novalinda Ginting; Thomson Parluhutan Nadapdap; Sherina Alfida (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Dental health is one of the factors supporting the healthy paradigm and is a national development strategy to achieve health development. Utilization of dental and oral public health services is crucial to maintaining dental and oral health. However, the low utilization of these health services remains a problem. This study aims to analyze the factors influencing the utilization of dental health services at Rengas Pulau Public Health Center. This type of research is an observational analytic study using a cross-sectional design. The study was conducted at Rengas Pulau Public Health Center from September 2023 to December 2023. The study population included all patients who visited Rengas Pulau Public Health Center more than once in 2023, totaling 151 patients. The research sample consisted of 60 people. The sampling technique used was accidental sampling. Data collection procedures were conducted through questionnaire interviews. Data analysis was performed using SPSS software, bivariate analysis using the chi-square test and multivariate analysis using multiple logistic regression with a significance level of 95% (α=0.05). The results showed that the factors influencing the utilization of dental health services at Rengas Pulau Public Health Center were distance from residence (ExpB= 3.527; p-value=0.003), the distance from the residence to the healthcare facility results in underutilization of dental health services; knowledge (ExpB= 3.158; p-value=0.005), people with good knowledge are more likely to utilize dental and oral health services because they understand that maintaining dental and oral health contributes to overall quality of life; and attitude (ExpB= 15.619; p-value=0.001), patients with a positive attitude will believe that undergoing an examination will significantly improve their dental and oral health, with the most dominant factor being patient attitude. It is recommended that Public Health Center improve health services by conducting socialization or outreach related to the available health services at the center. Keyword: Dental, Services, Utilization